Scaling the Climate-Smart Village model in national-level programs: The recommendations for adoption in the implementation of the Nông Thôn Mới (Vietnam’s National Target Program on New Rural Development) 2021-2030 Strategy - Bui, Le Vinh; Vu, Thanh Bien; Talsma, Tiffany; Spillane, Charles; Do, Thi Thu Ha; Nguyen, Tuan Cuong; Trieu, Hong Lua; Brychkova, Galina; McKeown, Peter; Nguyen, Thu Ha (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The New Rural Development Program or Nông Thôn Mới (NTM) is a national target program of Vietnam that has enabled 57% of rural communes to achieve the NTM status, which aims to raise the socio-economic standard of living of small communities while facilitating agricultural development. Agricultural development is threatened by the impacts of climate change, which carries high risk for an agriculture-dependent country like Vietnam. This Info Note discusses how the Climate-Smart Village (CSV) model can be applied in the NTM to help the communities under this program achieve “advanced” and “demonstration” status based on 19 criteria. Recommendations were listed on how to integrate the CSV model into the NTM.